2019
DOI: 10.7227/jha.014
|View full text |Cite
|
Sign up to set email alerts
|

Three Acts of Resistance during the 2014–16 West Africa Ebola Epidemic

Abstract: Community engagement is commonly regarded as a crucial entry point for gaining access and securing trust during humanitarian emergencies. In this article, we present three case studies of community engagement encounters during the West African Ebola outbreak. They represent strategies commonly implemented by the humanitarian response to the epidemic: communication through comités de veille villageois in Guinea, engagement with NGO-affiliated community leadership structures in Liberia and indirect mediation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
1
34
0
2
Order By: Relevance
“…Also, and despite the respite offered by the gradual advance of the pandemic, we have found that countries have taken a number of relatively similar -if not identical -health measures, which more fundamentally raises the question of the appropriateness of these measures to their national contexts and reawakens the myth of a "turnkey" response applicable to all and at all times. Yet all the scienti c literature on public health interventions, including in Africa [33,34] and on COVID-19 [13] a rms the importance of taking contexts into account in order for measures to be effective [35]. This need to contextualize the health response also requires taking into account the speci cities of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, and despite the respite offered by the gradual advance of the pandemic, we have found that countries have taken a number of relatively similar -if not identical -health measures, which more fundamentally raises the question of the appropriateness of these measures to their national contexts and reawakens the myth of a "turnkey" response applicable to all and at all times. Yet all the scienti c literature on public health interventions, including in Africa [33,34] and on COVID-19 [13] a rms the importance of taking contexts into account in order for measures to be effective [35]. This need to contextualize the health response also requires taking into account the speci cities of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, regarding containment measures, a scoping review synthesising relevant knowledge published in 2018 highlights the importance of community involvement for their effectiveness [36]. A study on Ebola in 2014-2016 in the region similarly showed the need for community involvement in disease control interventions that take into account local dynamics [34]. The analysis of the situation in ve African countries at the beginning of the pandemic also showed the importance of community involvement [10].…”
Section: Discussionmentioning
confidence: 99%
“…All articles were in English except for one, which was in French. 38 Thirty-two articles were included, but two articles report three 39 and four 40 distinct community engagement initiatives. As such, the remainder of the review will focus on 37 initiatives.…”
Section: Article Characteristicsmentioning
confidence: 99%
“…Specific make-up of community engagement approaches was often not detailed or did not include diversity and representation, though several reported community engagement structures, including representation from Ebola survivors, 56 women within reproductive age and students, 46 women representatives 39 and youth. 38 54 56 Health system linkages and support Of those that provided details on linkages, very few were explicitly linked to other health system components (with the exception of tracing).…”
Section: Target Groups and Equity Considerationsmentioning
confidence: 99%
“…This was a transformative policy approach, and because it correlated with the epidemic's decline, has been perceived to have facilitated the reduction in acts of direct violence and overt avoidance towards the public health response. 5 Decisions on whether or not to act on messages of public health campaigns are influenced by the level of auto nomous motivation to undertake behaviour change. [6][7][8] According to self-determination theory, 9 engagement in extrinsically motivated behaviours, such as participation in outbreak response efforts that are counter to personally or culturally satisfying practices, or both (eg, bushmeat consumption, traditional burials), would be increasingly enhanced and maintained as people identify with their value.…”
Section: Introductionmentioning
confidence: 99%